PENGARUH METODE DAN ARAH SADAP TERHADAP PRODUKSI GETAH JELUTUNG HUTAN TANAMAN INDUSTRI - Totok K. Waluyo; I. Wahyudi; G. Santosa (BRIN Publishing, 2012)
Jelutong gum is gum typifies excudates that result from the tapping of Dyera trees, Jelutong giam offers various uses, such as raw material of gom, a misture of automobile tire manufacture, rar material for making paints, adbesives and varnishes, The study was conducted to determine the method and direction of tapping on gum production from Industrial Plantation Forest's Jelutong Trees (HTI) The tapping methods performed are slicing with half spiral pattern from the upper left to the lower right (1/25 Kr Knj. slicing with